2008
DOI: 10.1159/000187631
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Transcutaneous Carbon Dioxide Tension Measurements during Cardiopulmonary Exercise Testing

Abstract: Background: Measurements of transcutaneous carbon dioxide tension (PtcCO2) with current devices are proven to provide clinically acceptable agreement with measurements of partial arterial carbon dioxide tension (PaCO2) in several settings but not during cardiopulmonary exercise testing (CPET). Objectives: The primary objective of this study was to investigate the agreement between PaCO2 and PtcCO2 measurements (using a Tosca 500 with a Tosca sensor 92) during CPET. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Earlier studies have also assessed the TOSCA system in different settings, but none have done this in a non-supervised continual measurement, while asleep, as in our study [3,7,8,9,10,11,12,13,14,15,18]. All referred studies performed measurements with a reported mean difference (bias) between PaCO 2 and PtcCO 2 ranging from 0.4 to 1.0 kPa (3 to 7.5 mm Hg).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have also assessed the TOSCA system in different settings, but none have done this in a non-supervised continual measurement, while asleep, as in our study [3,7,8,9,10,11,12,13,14,15,18]. All referred studies performed measurements with a reported mean difference (bias) between PaCO 2 and PtcCO 2 ranging from 0.4 to 1.0 kPa (3 to 7.5 mm Hg).…”
Section: Discussionmentioning
confidence: 99%
“…A maximum bias of <2 and 95% LOA of 4% were determined as clinically acceptable between arterial oxygen and transcutaneous saturation. To determine whether transcutaneous measurements differ significantly from the arterial values at the same time point we performed a Student’s paired t test [10]. Analysis of variance for repeated measurements was used to determine changes from one time point to the next.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies report a good correlation of PcCO 2 values with arterial blood gas measurements [16,17,18,19]. Similar to medical thoracoscopy and colonoscopy, bronchoscopy is also associated with an increase in PcCO 2 [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The system has been used in neonatological intensive care and in adult patients with acute respiratory or cardiac failure or during cardiopulmonary exercise testing [8,22,23,24]. The examinations consistently show a good correlation between Pa CO 2 and tcP CO 2 with a mean difference of 3 mm Hg.…”
Section: Introductionmentioning
confidence: 99%